The Triad of Governance, Devolution, and National Prosperity (The Pakistan Development Review, 2003)
I am privileged to have the opportunity to speak to this august audience of distinguished development economists very briefly, on what I have called the ‘Triad of Governance, Devolution and National Prosperity’. This, triad, I believe, lies at the heart of what constitutes the theme of this conference, namely ‘Institutional Change, Growth and Poverty’. The National Reconstruction Bureau which I was privileged to create and lead for all the three years of General Musharraf’s tenure as Chief Executive of Pakistan, was meant to transtate into reality the vision we crystallised for addressing the persistent failure of the institutions of state to provide solutions to the ever growing political, administrative, financial, judicial and social problems that the people of Pakistan faced since independence. The vision was ‘Reconstruction of the Institutions of State for Establishing Genuine and Sustainable Democracy to ensure Durable Good Governance for an Irreversible Transfer of Power to the People of Pakistan as soon as possible’. I will first give you a fleeting birds eye view of the wide spectrum over which our National Reconstruction endeavour in pursuit of this vision was spread. In the second part of this talk, which will contain the core of what I want to put across today, I will talk about financial devolution of the state. The third part of my talk will deal briefly with the burning issue of what we should do for turning our common citizens’ poverty into prosperity.